Biological Markers in Early Multiple Sclerosis: the Paved Way for Radiologically Isolated Syndrome - Rival, Manon; Galoppin, Manon; Thouvenot, Eric (Frontiers in Immunology, 2022)
Radiologically Isolated Syndrome (RIS) is a pre-symptomatic stage of multiple sclerosis (MS) characterized by MRI typical brain lesions fulfilling 2009 Okuda’s criteria detected in patients without clinical conditions suggestive of MS. Half of RIS subjects convert to MS within 10 years. However, individual course of disease is highly variable, 12% of RIS directly converting to progressive MS. Demographic and imaging markers have been associated with the risk of clinical MS in RIS: male sex, younger age, infra-tentorial and spinal cord lesions on the index scan, gadolinium-enhancing lesions on index or follow-up scans. Although not considered as a distinct MS phenotype, RIS certainly shares common pathological features with early active and progressive MS. There is a need to identify biomarkers that may refine the risk stratification for clinical MS and disability for early treatment. Intrathecal B-cells activation with cerebrospinal fluid (CSF) oligoclonal bands, elevated kappa free light chains and cytokine production is specific of MS while neurofilament light chain (NfL) levels rather reflect disease activity associated neuroaxonal injury. Specific MicroRNA profiles have been identified in RIS converters both in CSF and blood. CSF levels of chitinases and glial acidic fibrillary protein (GFAP) reflecting astrogliosis might help predict RIS evolution to progressive MS. Innovative genomic, proteomic and metabolomic approaches provided several new candidate biomarkers to be explored in RIS. Leveraging data from RCTs and large prospective RIS cohorts with extended follow-up to identify earliest biomarkers predicting greater disease severity would be invaluable to counsel patients and manage treatment and monitoring.